Алгоритм синтеза линейных антенных решеток c требуемой диаграммой направленности и целочисленными амплитудными коэффициентами - Садченко, А.В.; Кушниренко, О.А.; Троянский, А.В. (Технология и конструирование в электронной аппаратуре, 2015)
Предложен алгоритм синтеза эквидистантных линейных решеток с действительными амплитудными коэффициентами и ограниченным набором фазовых коэффициентов, а также модификация данного алгоритма для случая целочисленных значений затухания аттенюаторов антенной решетки. В основе алгоритма лежит дискретное Фурье-преобразование функции, описывающей требуемую диаграмму направленности решетки. Запропоновано алгоритм синтезу еквідистантних лінійних решіток з дійсними амплітудними коефіцієнтами і обмеженим набором фазових коефіцієнтів, а також модифікацію даного алгоритму для випадку цілочислових значень згасання аттенюаторів антенної решітки. В основі алгоритму лежить дискретне Фур'є-перетворення функції, яка описує необхідну діаграму спрямованості решітки. This study aims to develop a search algorithm for amplitude and phase coefficients, taking into account the fact that integer-valued amplitudes and phases are technically easier to implement than real ones. Synthesis algorithm for equidistant linear array with a half-wavelength irradiators pitch (&l;/2) is as follows. From a given directivity function the discrete Fourier transform (DFT) in the form of an array of complex numbers is found, the resulting array is then transformed into a set of attenuations for attenuators and phase shifts for phase shifters, while the amplitude coefficients are rounded off to integers, and phases are binarizated (0, ?). The practical value of this algorithm is particularly high when using controlled phase shifters and attenuators integrally. The work confirms the possibility of a thermoelectric converter of human body application for an electronic medical thermometer power supply.